THE EFFECT OF DEBT TO EQUITY RATIO, CURRENT RATIO, AND DEBT TO ASSETS RATIO ON RETURN ON ASSETS IN NON FINANCIAL COMPANIES LISTED ON THE LQ45 INDEX AND THE SET50 INDEX - Dwi Faradiba Siregar; Iskandar Muda; Yeni Absah (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to examine and analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Debt to Assets Ratio (DAR) on Return on Assets (ROA) in non-financial companies listed on the LQ45 index in Indonesia and the SET50 index in Thailand during the 2022–2024 period. This research employed a quantitative approach using secondary data obtained from companies' financial statements. The purposive sampling technique yielded 18 LQ45 companies and 35 SET50 companies, with a total of 159 observations. Panel data regression using EViews software was applied, alongside the Mann–Whitney difference test. Results indicate that for LQ45 companies, DER has a positive but insignificant effect on ROA; CR has a positive and significant effect on ROA; and DAR has a positive but insignificant effect on ROA. For SET50 companies, DER has a negative but insignificant effect on ROA; CR has a positive and significant effect on ROA; and DAR has a negative but insignificant effect on ROA. Simultaneously, DER, CR, and DAR do not significantly affect ROA in LQ45 companies but significantly affect ROA in SET50 companies. The Mann–Whitney test reveals significant differences in DER, DAR, and ROA between LQ45 and SET50 companies, while CR shows no significant difference. These findings indicate that liquidity plays a crucial role in improving profitability in both indices, while the effect of debt structure on profitability differs according to market and firm characteristics.